A qualitative study of women's experience of a perinatal group health-promoting programme. (2nd February 2019) - Buultjens, Melissa; Murphy, Gregory; Ruddock-Hudson, Mandy; Milgrom, Jeannette; Taket, Ann
Abstract : Background: Antenatal and parenting programmes are a way of supporting and empowering parents. However, not all informational needs are being met, and nor are programmes equipping women with skills and confidence to meet the challenges of parenthood. Aims: To explore women's experiences of participating in a group psycho-educational programme across their pregnancy and early postnatal period. Methods: A qualitative descriptive design was applied, incorporating thematic analysis to identify themes in the data. Findings: The programme demonstrated practical benefits such as dissemination of timely information, continuity of care and professional support. It enabled opportunities for mastering new tasks and increased a woman's social support network. Conclusion: Focusing on the entire perinatal period can promote better perinatal health and psychosocial outcomes.